Antioxidant components of the three different varieties of Indonesian ginger essential oil: In vitro and computational studies - Badrunanto; Wulan Tri Wahyuni; Muhammad Farid; Irmanida Batubara; Kosei Yamauchi (Food Chemistry Advances, 2024)
Differences in antioxidant activity and the components that contribute to this activity in the essential oil (EO) of three varieties of Indonesian ginger were studied. The EOs were isolated at various distillation times and their composition was identified by GCMS. Antioxidant activities were determined by in vitro analysis, while Pearson correlation followed by density functional theory (DFT)-based reactivity descriptors analysis was used to identify their antioxidant components. A total of 29 components were identified from all studied ginger EOs where geranial was main component of red (28.3 %) and gajah ginger (20.4 %), while zingiberene (16.2 %) was main component of emprit ginger EO. In general, the gajah ginger EO was demonstrated the best antioxidant activity. Pearson correlation analysis was revealed 9 components, namely β-myrcene, D-limonene, α-sabinene, geranyl acetate, α-curcumene, α-zingiberene, α-farnesene, β-bisabolene, and β-sesquiphellandrene, may be contribute for antioxidant activity with strong correlation value (r>0.6). Reactivity descriptors of B3LYP optimized geometry and DEF2-SVP basis set confirmed the reactivity of the nine components and revealed zingiberene as the most reactive. This study has revealed the differences in antioxidant activity and antioxidant components of Indonesian ginger EOs, thus providing clearer information regarding the best variety and composition profile as a natural antioxidant ingredient.